S.B.E. (Pvt.) Ltd : The Focused Selling Approach - Amir, lrfan (Gyan Management Journal, 2007)
In order to achiev sales growth Unjl ver Pakistan Limited (UPL) launched Project Fetwri in July 2002. The launch was a culmination of preparatory work O’:er a p riod of a year and a half. A significant invesrment in terms of tim